Charm++ and AMPI: Adaptive Runtime Strategies via Migratable Objects - Kale, Laxmikant V.; Zheng, Gengbin (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction The Programming Model Automatic Adaptive Overlap: Adapting to Communication Latencies and Response Delays Adapting to load Variations in the Application Adapting to Changing Number of Available Processors Adaptive Communication Optimizations Adapting to Available Memory “Adapting” to Faults Language Extensions Summary References